Student’ Adjustment to Changes in Online to Offline Learning at SMP Pasundan II Garut District Garut Regency - Nurjanah Nurjanah (Politeknik Kesejahteraan Sosial Bandung, 2023)
Online learning since the Covid-19 pandemic has demanded adjustments for students in the online learning process, but when entering education for the 2021/2022 school year, several schools in Indonesia have started Face-to-face Learning (PTM) so students must immediately make adjustments in the learning process in Indonesia class. As a general formal education institution, SMP Pasundan II Garut, students are always required to be able to adapt to current conditions in the school environment. Students' enthusiasm for learning decreases and they become less disciplined towards the PTM process in class due to habits in the previous online learning process. This study is intended to determine the adjustment of students who are following the PTM process at SMP Pasundan II Garut. The aspects that are examined in this student's adjustment are adjustment to real appearance, groups, social attitudes and personal satisfaction. This research uses quantitative methods and this type of research uses census research with quantitative descriptive methods. The sample in this study were all 52 students. Data collection techniques using questionnaires and documentation studies. Based on the results of the study, it showed that self-adjustment to the real appearance was in the moderate category, namely 1,098 points, for the low category group, namely 1,011 points, for social attitudes in the low category, namely 944 points, for personal satisfaction was in the high category, namely 1,197 points. students have a tendency towards personal satisfaction. Pasundan II Junior High School students still have not made good adjustments to changes in online to offline learning. The researcher's suggestions relate to development policies & programs that touch students' self-adjustment in the face-to-face learning process. Further research on self-adjustment needs to be carried out with research subjects of students in schools who have just implemented face-to-face learning, especially in remote areas. Keywords: Adaptation, Students, Changes in Online to Offline Learning, Pasundan II Middle School